'Street Blues. The Experiences of a Reluctant Policeman.' By Andrew Brown; 'Gangs, Politics and Dignity in Cape Town.' By Steffen Jensen; 'Thin Blue, the Unwritten Rules of Policing in South Africa.' By Jonny Steinberg. - Fourchard, Laurent (Kronos: Southern African Histories, 2017)
These three recent books have in common the question how men and women in post-apartheid South Africa face a violent environment and how they build a sense of order. These stories are related to a specific urban environment (in or around Cape Town and Johannesburg) in which violent crime has a long history, except in white suburbs where violent crime according to Andrew Brown, Jonny Steinberg and others is mainly a post-apartheid concern.